Both Dissolved Oxygen and Chlorophyll Explain the Large-Scale Longitudinal Variation of Deep Scattering Layers in the Tropical Pacific Ocean - Song, Yuhang; Wang, Chunsheng; Sun, Dong (Frontiers in Marine Science, 2022)
The ecological characteristics of mesopelagic community are crucial to understand the pelagic food web, replenishment of pelagic fishery resources, and building models of the biological pump. The deep scattering layers (DSLs) and diel vertical migration (DVM) are typical characteristics of mesopelagic communities, which have been widely observed in global oceans. There is a strong longitudinal environmental gradient across the tropical Pacific Ocean. Nevertheless, the longitudinal variation of DSLs along this gradient was still largely unclear until now. We investigated the DSLs across the tropical Pacific Ocean using data of shipboard acoustic Doppler current profiler at 38 kHz from July to December 2019. The study area was divided into three sub-regions by cluster analysis of environmental variables: the western part (WP), the transition part (TP), and the eastern part (EP). The result confirmed that the longitudinal variation of DSLs and DVM: the weight migrating depth of mesopelagic organisms was reduced from 571.2 ± 85.5 m in the WP to 422.6 ± 80.8 m in the EP; while the migrating proportion was minimum in the TP (35.2 ± 12.8%), and increased to 86.7 ± 16.2% in the EP. Multiple regressions analysis showed that both the mesopelagic average oxygen and chlorophyll a concentration were significant factors which influenced the upper boundary depth and weight migrating depth, while the center mass depth was only influenced by the chlorophyll a. Since higher demand of most predators of mesopelagic animals for dissolved oxygen and light intensity, the limitations of predator behavior by environmental conditions might explain the observed spatial heterogeneity of DSLs. Combining the previous results and the findings of this study, it implied that declined biomass, shallower habituating depths, and lower migration proportion of mesopelagic animals under more extremely oligotrophic conditions with global change in future, would reduce the active carbon flux and hinder food supply to deep-sea biological communities in the tropical Pacific Ocean.